If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = -3(5y + 2) Reorder the terms: 23 = -3(2 + 5y) 23 = (2 * -3 + 5y * -3) 23 = (-6 + -15y) Solving 23 = -6 + -15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15y' to each side of the equation. 23 + 15y = -6 + -15y + 15y Combine like terms: -15y + 15y = 0 23 + 15y = -6 + 0 23 + 15y = -6 Add '-23' to each side of the equation. 23 + -23 + 15y = -6 + -23 Combine like terms: 23 + -23 = 0 0 + 15y = -6 + -23 15y = -6 + -23 Combine like terms: -6 + -23 = -29 15y = -29 Divide each side by '15'. y = -1.933333333 Simplifying y = -1.933333333
| 66y/3-34y | | 8x^2-128x=0 | | 1+6y-15y= | | 1/3-K/8=7/24 | | -1(-1y+3)=1 | | -.4x^2+.2x=-2 | | 4x^2+10=-14x | | 2x^3/5=54 | | 3(x+4)+2x=2 | | 11-x=7+3x | | 5(0)-2=4-3(0)+2 | | 24=-3+6(v+7) | | 7(-3)+20=2(-3)+5 | | x^3=6x^2-36x-60 | | 7y^2-7=144 | | 9x^2-74x+16=0 | | -50-2x=-290 | | 6s+7-9s=31 | | X^2+5x+15x=0 | | t-1/3=1/4 | | -300m-4p=10p | | K^1/3/k^2/3k-1 | | 2f+8=3f-4 | | 3/1-√19 | | 2x=y/(y-1)-3 | | 2(3y-10)=4y+26 | | 23=2x+8+x | | (x-3)2+5x=(x+2)2-5 | | Q=5aP^2+9bP^3 | | 4y-3+y+37=8y+40-6y | | 3a-2b-c=0 | | 6x^2y^3+10x^2y^2k-30x^3y^2-2xy^3= |